Political Polarization and the Disruption of Digital Democracy in Indonesia: A Critical Reassessment of Political Science Perspectives - Miinudin; Luthfi Muhyiddin; Rahmat, Maulana Bagus Rahmat (JURNAL TAPIS, 2026)
The digital era has fundamentally transformed Indonesia's political landscape, shifting the arena of contestation from physical spaces to complex algorithmic environments. The emergence of intense polarization, exacerbated by social media echo chambers and systematic information disruption through buzzers and bots, demands a paradigm shift in political science. This study aims to analyze the dynamics of digital polarization and its implications for democratic governance in Indonesia. Using a qualitative approach with a systematic literature review, this study analyzes approximately 140-150 academic sources (journal articles and books) published between 2021–2025. The literature selection is based on relevance to digital democracy, polarization, and computational politics, as well as credibility indexed in reputable academic databases. The analysis employs a thematic approach to identify recurring patterns related to algorithmic influence, affective polarization, and digital manipulation strategies. The results indicate that digital disruption in Indonesia is driven by algorithmic engineering that exploits social identities and amplifies emotional sentiments, leading to affective polarization. Furthermore, the use of cyber troops and astroturfing systematically undermines democratic deliberation by producing pseudo-public opinion. This study concludes that political science must evolve by integrating Computational Social Science and digital sociology to remain relevant in analyzing contemporary power structures. The research contributes theoretically by introducing an algorithmic perspective on political power and practically by offering a framework for strengthening democratic resilience in the digital age.